Peningkatan Kompetensi Bahasa Inggris bagi Dosen FKIP Universitas Mathla’ul Anwar Banten - Ade Sudirman; Nur Azmi Rohimajaya (Jurnal Pengabdian Pada Masyarakat, 2018)
THE IMPROVING OF ENGLISH COMPETENCE FOR LECTURERS OF FACULTY OF TEACHER TRAINING AND EDUCATION OF UNIVERSITY OF MATHLA’UL ANWAR BANTEN. This community service activity is motivated by the thought that the need for lecturers to have good competence in using English in the teaching and learning process in the classroom. With the hope that through its application, students become more enthusiastic in learning. The purpose of this community service activity is to provide scientific assistance to the lecturers of FKIP Unma Banten in using English in the teaching and learning process. While the benefits of this activity are to have a positive effect on the lecturers of FKIP Unma Banten in communicating using English in class and the increasing enthusiasm and achievement of FKIP Unma Banten students in learning. This service activity was carried out in the form of short training for two meetings with members of 10 lecturers held in the hall of FKIP Unma Banten. The first meeting discussed the importance of English, introducing word, clause, and sentences, mastering tenses by using smart fingers technique. The second meeting was a deepening of the material followed by the practice of TOEFL questions and the practice of speaking English in everyday life with simple sentences by participants of FKIP Unma Banten lecturers. The method used in this community service activity is the lecture method, question and answer, discussion and demonstration methods. Based on observations during this community service activity, several positive results were obtained. The results of this community service are the increased insight of FKIP Unma Banten lecturers on English language material and its application in the teaching and learning process in the classroom.